2012
DOI: 10.1097/eja.0b013e32834b7d65
|View full text |Cite
|
Sign up to set email alerts
|

Point-of-care prothrombin time testing in paediatric intensive care

Abstract: CoaguChek XS Plus showed 'good' agreement, whereas CoaLine showed 'moderate' agreement compared with prothrombin time values using the standard method. The fast availability of results and the reduction of the required blood volume are advantages of point-of-care tests in the paediatric setting.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(2 citation statements)
references
References 17 publications
0
2
0
Order By: Relevance
“…The failure rate of measuring INRs by the CoaguChek XS was 2% in our study. A previous study in a pediatric population demonstrated that failure rates were 2% with CoaguChek XS and 4% in the laboratory test [22]. One limitation of this study is that CoaguChek XS INR was measured by a small group of trained neonatologists.…”
Section: Discussionmentioning
confidence: 94%
“…The failure rate of measuring INRs by the CoaguChek XS was 2% in our study. A previous study in a pediatric population demonstrated that failure rates were 2% with CoaguChek XS and 4% in the laboratory test [22]. One limitation of this study is that CoaguChek XS INR was measured by a small group of trained neonatologists.…”
Section: Discussionmentioning
confidence: 94%
“…Several studies have evaluated the clinical use of the CoaguChek XS Plus system [10, 1317]. Those studies were performed in different clinical settings using different laboratory-based tests, and only one of them compared the CoaguChek XS Plus system with the Stago coagulation system (Table 2).…”
Section: Discussionmentioning
confidence: 99%